Analysis on Competition Type between Fixed and Mobile Broadband Service in Indonesia - Wirianto Pradono (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2021)
Both fixed and mobile broadband technologies are adopted in Indonesia. This study aims to identify the competition model between both of them. Non-linear exponential model is employed to estimate diffusion pattern of both broadband services. Meanwhile, Lotka-Volterra method is applied to identify competition model between those two. Results of the study show that for Indonesia telecommunication market, competition relationship between fixed and mobile broadband are mutualism or win-win solution. Considering topography of the regions of Indonesia especially those categorized as rural area, the existence of both fixed and mobile broadband technologies are crucial to accelerate the distribution of the equal access to broadband internet for all Indonesia people both in urban and rural areas. This becomes more urgent when commercial 5G services is deployed in Indonesia.